A PHENOMENOLOGICAL STUDY OF INSTAGRAM FASTING ON MILLENNIAL - Eny Ratnasari; Fikri Dwi Oktaviani (IAIN Salatiga, 2019)
The aims of this study is to find out: (1) the background of doing Instagram fasting; (2) things that were felt before doing Instagram fasting. The main reason for this millennial generation to do Instagram fasting is the discomfort of the experience of using Instagram. The informants agreed that Instagram is currently becoming poisonous or toxic which has a negative impact on their psychological. They seemed to be chased by something that was so obsessed that they were afraid to miss something or Fear of Missing Out (FOMO). After fasting, the informants claimed productivity increased, distraction decreased, more positive thinking.